LIFI : LIGHT FIDELITY IN THE SCHOOL LIBRARY - Muhaimin Hasanudin; Boy Yuliadi (IJISCS (International Journal of Information System and Computer Science), 2021)
Light is energy lighting that can be used to transmit data and can reduce the use of the access point for local access in a building. The purpose of this paper is to implement technology Light Fidelity (Li-Fi) on the school library. Li-Fi has a very high potential in generating the connection data delivery fast. Li-Fi is even referred to as a technology that is better or superior than Wi-Fi (Wireless Fidelity). This is due to the broad scope of the installation is wider than Wi-Fi as well as the speed of sending data that far exceeds the Wi-Fi.  Wi-Fi uses radio waves as a mediator while Li-Fi uses light as a mediator to transmit data. For installation its own Li-Fi using tools such as server, lamp driver, Li-Fi dongle, as well as the device to be connected, such as computers, smartphones, and tablets.